1978
DOI: 10.1002/pssa.2210460228
|View full text |Cite
|
Sign up to set email alerts
|

On annealing-induced prismatic dislocation loops and electrical changes in heavily Te-doped GaAs

Abstract: The nature of the perfect prismatic dislocation loops formed during the post‐growth annealing treatments of moderately heavily Te‐doped (viz. 1018cm−3≦[Te]≦ 8 × 1018cm−3) GaAs in the temperature range 800 to 1000 °C is determined by transmission electron microscopy. The results of the detailed diffraction contrast analysis show unambiguously that these defects are vacancy type in character contradicting an earlier conclusion that the prismatic loops are interstitial type. A divacancy‐model is proposed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Another type of defects :which could contain an impurity [6] are precipitates on, dislocation loops, visible" in Fig. '.l and': in high resolution mode in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another type of defects :which could contain an impurity [6] are precipitates on, dislocation loops, visible" in Fig. '.l and': in high resolution mode in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Prismatic dislocation loops on {110} planes and faulted loops on {111} planes were interpreted as vacancy type loops [6] or as interstitial type loops [1]. It was suggested [1] that faulted loops on {111} planes contain platelet shape Ga-Te precipitates resulting from decomposition of supersaturated solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…Kamejima et al (1979) identified interstitial type prismatic loops in S-doped GaAs. Recently Hughes and Narayanan (1978) investigated Te-doped GaAs and disagreed with the interstitial identification of the prismatic loops and concluded that they were indeed vacancy type.…”
Section: Experimental Observation Of Point Defects In Gaasmentioning
confidence: 99%
“…A plausible reason could be differences in the starting material and/or the different methods of preparation of the samples for the annealing treatments. For example, while Hughes and Narayanan (1978) cleaned their samples and the quartz tubes used for the annealing experiments in aqueous KCN solution to reduce possible Cu contamination such a procedure was not followed by Dobson (1974, 1975a.). It is worthwhile to mention here that the controversy of vacancy type versus interstitial type prismatic dislocation loops also exists in another III-V compound viz.…”
Section: Experimental Observation Of Point Defects In Gaasmentioning
confidence: 99%
“…7 for Te-doped GaAs. A number of investigators of similar materials (Hutchinson & Dobson, 1975;Wagner, 1977;Hughes & Narayanan, 1978) have noted the occurrence of precipitates on dislocation loops. Some of these investigators have concluded that the precipitates are associated with the dopant, either as a Te rich complex or as microprecipitates of GaTe.…”
Section: Identification Of Precipitatesmentioning
confidence: 99%